Linguistic Validation of the Canine Brief Pain Inventory (CBPI) for Global Use - Wells, Jane R.; Young, Alyson L.; Crane, Alexandra; Moyaert, Hilde; Michels, Gina; Wright, Andrea (Frontiers in Veterinary Science, 2021)
A valid and reliable quantitative measure of chronic pain is essential for developing and evaluating interventions that aim to treat pain. In dogs, the Canine Brief Pain Inventory (CBPI) was originally adapted from a human measure, the Brief Pain Inventory, to assess owner-perceived pain and the impact of such pain on a dog’s daily functioning. To be reliable and valid, data collected using a translated instrument should have evidence it is an accurate representation of the original instrument and is culturally appropriate for use in the intended context. To achieve this, instruments should undergo a rigorous translation process and be debriefed in the intended population of use. The CBPI is widely accepted and has been fully validated for use in US-English, Swedish and French (France); further translation and validation of the CBPI is required to increase access to and use in other languages and countries. The objective of this study was to linguistically validate the CBPI for global use (Australia, China, Germany, Hungary, Ireland, Japan, Netherlands and Portugal). In cognitive debriefing with a representative sample of dog owners in the target countries it was confirmed that the translations of the CBPI adequately convey the concepts in the original US-English version and that items are easily understood by dog owners. The results of the linguistic validation process thus produced measures that are conceptually equivalent to the original US-English-language CBPI and are culturally appropriate for use in the target countries.